Identification of Potential Binding Sites of Sialic Acids on the RBD Domain of SARS-CoV-2 Spike Protein - Li, Bingqian; Wang, Lin; Ge, Huan; Zhang, Xianglei; Ren, Penxuan; Guo, Yu; Chen, Wuyan; Li, Jie; Zhu, Wei; Chen, Wenzhang; Zhu, Lili; Bai, Fang (Frontiers in Chemistry, 2021)
COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is still an emergent pandemic for humans. The virus infection is achieved by penetrating its spike protein to host cells via binding with ACE2. Moreover, recent studies show that SARS-CoV-2 may have multiple receptors that need to be further revealed. SARS-CoV-2 shares similar sequences of the spike protein with the Middle East Respiratory Syndrome Coronavirus (MERS-CoV), which can invade host cells by binding to either DPP4 or sialic acids. Sialic acids can be linked to the terminal of glycoproteins and gangliosides are used as one of the receptors of many types of viruses. Therefore, it is very interesting to determine whether sialic acid is a potential receptor of SARS-CoV-2. To address this question, we took N-Acetylneuraminic acid (Neu5Ac), a type of predominant sialic acid found in human cells, as the molecular probe to computationally search the surface of the spike protein to locate the potential binding sites of Neu5Ac. SPR analysis and mass spectrum analysis confirmed the interaction between Neu5Ac and spike protein. This study shows that sialic acids can moderately interact with the spike protein of SARS-CoV-2 by binding between the two RBDs of the spike protein, indicating it could be a potential secondary or auxiliary receptor of SARS-CoV-2.